Role of ketogenic diet and its effect on the periodontium. A scoping review - Taher, Hala Al; Salah, Aya; Rammal, Caroline; Varma, Sudhir Rama (Frontiers in Oral Health, 2024)
The purpose of this study is to investigate the relationship between the ketogenic diet and periodontitis, as well as the nature of such relationship. Furthermore, emphasis was given to know whether ketogenic diet causes changes in oral health parameters and more specifically on periodontal health. Studies from 2010 to 2023 were reviewed and analyzed. Databases used to search included PubMed, Mednet, Scopus, Cochrane, and Embase. The literature reviewed was limited to randomized clinical trials, observational studies, and case-control studies. Of the eight studies included, three studies found that diets with similarities to the ketone-based diet could have a significant positive impact on periodontal health. One study pointed to the potential positive effect of a diet such as keto, but no definitive conclusion could be made. The current body of evidence concluded that there may be a relationship between keto and periodontitis, although the evidence is not consistent. It can be implied, however, that it is a positive relationship as ketogenic diet has been shown to have an anti-inflammatory effect, reducing inflammatory markers found in many diseases, including periodontitis. Commented [DSV1]: Reviewer 1-Explanation of Figure 1 in the main manuscript file should be more descriptive Commented [DSV2R1]: Sentences are added regarding Fig 1 as advised Commented [DSV3]: Reviewer 2-Phytochemical compounds found in plants have health-promoting properties, antioxidant, anti-inflammatory, and anticancer effects and are detrimental to overall health. [7] Detrimental -Pl CLARIFY